ANALISIS PRODUKSI UBI JALAR DI DESA PULU KECAMATAN DOLO SELATAN KABUPATEN SIGI - Reni dian sari. Darise; Sulaeman Sulaeman (Universitas Tadulako, 2015)
This study aimed to determine the effect of land, seed, fertilizer, labor, length of education, farmingexperience and number of farm family dependents on sweet potato production in Pulu village South Dolo Sub District Sigi Regency. The study was conducted in July to August 2014 with 31 respondents as samples selected from about 105 people who cultivated sweet potato using a simple random sampling technique. The analysis showed that simultaneously land area (X1), seeds (X2), fertilizers (X3), labor (X4), length of education (X5), farming experience (X6) and the number of dependents (X7) very significant affected the production of sweet potato, with the F-count> F-table (36.496 ≥ 0.892) at the level of α 1%.The results of t-test showed that partially,land area, seed, fertilizer, labor, length of education, and farming experience are significantly affect the potato production at the α level of 1% whereas the number of dependents is not significant. Keywords: Production sweet potato, Pulu Village.